1998
DOI: 10.5059/yukigoseikyokaishi.56.940
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Study of Marine Polycyclic Ethers: Total Synthesis of Hemibrevetoxin B.

Abstract: Abstract:Two efficient methods for the synthesis of the cyclic ethers, the important fundamental components of marine polycyclic ethers, were developed: (1) rearrangement-ring expansion reaction and (2) endo-cyclization of hydroxy styrylepoxide. Based on the newly developed methods, stereoselective total synthesis of hemibrevetoxin B (2) has been completed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…[27][28][29][30][31][32] In 1997, Nakata and co-workers reported that introduction of a styryl group adjacent to the epoxide provided greater stabilisation in the 6-endo transition state compared with the alkenic epoxides. 33,34 Treatment of trans-epoxides containing a styryl group with either acid or base generated THP products in excellent yield, but improved stereocontrol was achieved using NaH (entries 1 and 2, Table 1). Whilst Nicolaou reported that unsaturated cis-epoxides gave poor 6-endo selectivity under acidic conditions, 23 Nakata showed that styryl epoxides may be converted solely to THP products under acidic conditions, with no evidence for the formation of the corresponding THF (entries 3 and 4, Table 1).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[27][28][29][30][31][32] In 1997, Nakata and co-workers reported that introduction of a styryl group adjacent to the epoxide provided greater stabilisation in the 6-endo transition state compared with the alkenic epoxides. 33,34 Treatment of trans-epoxides containing a styryl group with either acid or base generated THP products in excellent yield, but improved stereocontrol was achieved using NaH (entries 1 and 2, Table 1). Whilst Nicolaou reported that unsaturated cis-epoxides gave poor 6-endo selectivity under acidic conditions, 23 Nakata showed that styryl epoxides may be converted solely to THP products under acidic conditions, with no evidence for the formation of the corresponding THF (entries 3 and 4, Table 1).…”
Section: Reviewmentioning
confidence: 99%
“…This methodology was used in the synthesis of a model compound 170 with the ST rings of maitotoxin (Scheme 37). 34,97 Zinc acetate in refluxing acetic acid was required for the ring expansion of mesylates 166 and 169. However, Nakata showed that by using chloromethylsulfonate (Mc) as the leaving group, rather than mesylate, ring expansion was achieved without the need for acetic acid (Scheme 38).…”
Section: Expansion Of Thf Ringsmentioning
confidence: 99%
See 1 more Smart Citation
“…When treated with Jacobsen catalyst 148 - 4 , diepoxide 148 - 1 was selectively transformed to diol 148 - 2 in 98% yield. This diol was efficiently protected to form 148 - 3 , intercepting a late-stage intermediate in Nakata’s total synthesis of hemibrevetoxin ( 148 - 5 ) …”
Section: The Jacobsen Hydrolytic Kinetic Resolutionmentioning
confidence: 99%
“…This diol was efficiently protected to form 148-3, intercepting a late-stage intermediate in Nakata's total synthesis of hemibrevetoxin . 801 The hydrolytic kinetic resolution of epoxides has been widely employed in the early steps of many total syntheses to generate enantiopure epoxide or epoxide-derived starting materials. The generality of this resolution has led to its widespread adoption; Jacobsen has written that "virtually every terminal epoxide examined to date [undergoes] clean and highly selective resolution."…”
Section: The Jacobsen Hydrolytic Kineticmentioning
confidence: 99%